Investigating the Prevalence of Headache and Its Influencing Factors in the Intensive Care Unit - Seyed Hossein Aghamiri; Ali Erfani; Milad Borji (Archives of Anesthesia and Critical Care)
Background: Headache may be aggravated by factors such as contracting new diseases, taking medications, or being hospitalized. One of the diseases that is effective in causing pain, especially headaches in patients, is the Covid-19 disease. for this reason, this study was conducted with the aim of the prevalence and factors affecting headache in covid-19 patients admitted to the ICU. Methods: This study is a part of the registry related to covid-19 patients, and the researchers analyzed the data after obtaining the code of ethics in the research. in this study, the tool that was used included a demographic profile form and a checklist for examining pain and its influencing factors in patients admitted to the ICU.  data analysis was done using SPSS version 16 software and independent t-tests, ANOVA, linear regression and confirmatory statistics. Results: Result showed 1114 (78.8%) of the patients reported headache and 300 (21.2%) of the patients had no complaints about headache. regarding the type of pain, it was shown that 341(30.6%) had Pressure type, 360(32.3%) had Tightening type, 335(30.1%) had Throbbing type and 78(7%) had Irritability type. Also, in relation to the duration of pain, it was shown that 228(20.5%) had pain less than 1 hour, 171(15.4%) had pain between one hour and 24 hours and 715(64.2%) had pain more than 24 were hours. Also, 178(16%) of the patients had moderate headache and 936(84%) of the patients had severe headache. Conclusion: Considering the high prevalence of headache in patients with covid-19 hospitalized in the ICU, it is necessary to take necessary intervention measures to reduce the patient's headache.